Tibet a history - Van Schaik, Sam.; ebrary, Inc. (New Haven : Yale University Press, 2011)
Presents a comprehensive history of the country, from its beginnings in the seventh century, to its rise as a Buddhist empire in medieval times, to its conquest by China in 1950, and subsequent rule by the Chinese.
Tibet appears, 600-700 -- The holy Buddhist empire, 700-797 -- Keepers of the flame, 797-1054 -- Patrons and priests, 1054-1315 -- Golden age, 1315-1543 -- The rise and fall of the Dalai Lamas, 1543-1757 -- The balancing act, 1757-1904 -- Independence, 1904-1950 -- Under the Red Flag, 1950-1959 -- Two Tibets, 1959 to the present.
Includes bibliographical references (p. 292-303) and index.
Electronic reproduction.
Keywords: Tibet Autonomous Region (China) -- History; Electronic books